PENGARUH DISIPLIN, SEMANGAT KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KLINIK INSANI MUARA TEWEH - Sri Yunida; Muhammad Harlie; Husnurrofiq Husnurrofiq (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
Insani clinical Muara Teweh founded in 2014 and until now more or less run for two years, address at T. Surapati street RT.12A Malayu village Muara Teweh North Barito regency in Central Kalimantan. With the number of employees 50 people managed by Heriansyah.This study aims to determine the effect of discipline, spirit of work and working environment together and partially on the performance of employees in Insani clinical Muara Teweh. This type of research is quantitative method. The samples were obtained 50 votes. To determine the effect of the influence of discipline, spirit of work and working environment to employees performance at Insani clinical Muara Teweh statistical methods used multiple linear regression test. Data processing was performed using IBM SPSS Statistics 23 program for Windows.Based on the results of the research show that together the discipline, spirit of work and working environment significantly influence employee performance in Insani clinical Muara Teweh. Partially, discipline, morale and working environment positive and significant effect on the performance of employees in Insani clinical Muara Teweh.